Africa [videorecording (DVD)] : eye to eye with the unknown - Attenborough, David, 1926- (BBC Earth., 2013)
Africa is a six-part series that will amaze and awe with stunning photography and truly moving stories of survival on the continent with the most diverse animal life anywhere on our planet.